Pilot test of low-rank coal pyrolysis coupled with gasification to hydrogen-rich gas for direct reduced iron: Process modeling, simulation and thermodynamic analysis. (1st January 2023) - Liu, Qian; Zhao, Ying-jie; Huang, Yi; Pei, Feng; Cui, Yang; Shi, Li-juan; Chang, Li-ping; Yi, Qun
Graphical abstract: Highlights: A low-rank coal pyrolysis coupled with gasification for DRI system is proposed. Effects of the key parameters on CCHI process are optimized and analyzed. CCHI is more energy/exergy-saving compared to traditional coking-BF iron-making. CO2 emission is reduced by 763.5 kg/ t -iron compared to coking-BF iron-making. Abstract: A Coal-Coke-Hydrogen-Iron (CCHI) system, low-rank coal pyrolysis coupled with gasification based on pilot test to hydrogen-rich gas for direct reduced iron (DRI), was proposed. The new process creatively proposes to blend the pyrolysis gas produced by pyrolysis of non-coking coal with the gasification gas produced by gasified coke to obtain the reducing gas that can meet the requirements of the DRI technology, addressing the problems of overcapacity in the coking industry and high carbon emissions in the steel industry. A strategy of partial cycle of top gas (rich in H2 and CO) from the shaft furnace is adopted to improve gas utilization and reduce carbon emissions, which is named as CCHI system with top gas cycle (CCHI-WTC) system. The key operation parameters and conditions such as steam/coke ratio, oxygen/coke ratio, reforming ratio and circulation ratio are optimized at 0.98, 0.43, 1.00 and 12.33 %, under which the energy consumption per unit product, exergy loss per unit product and greenhouse gas unit product emission of CCHI-WTC system can reach 15.13 GJ/t, 7.85 GJ/t and 761.50 kg/t, being reduced by 24.16 %, 20.14 % and 50.01 % compared to the traditional Coking-Blast furnace ironmaking process, respectively. This work provides a new low-rank coal application approach and breaks down the industry barriers of coal chemical industry and metallurgy.